(untitled) (diségno, 2023)
The National Conference on the Didactics of the Figurative and Performing Arts ARTEDU, took place at the Faculty of Education of the Free University of Bozen on 14 and 15 December 2022 in Brixen, under the scientific responsibility of professors Alessandro Luigini (Graphic and visual sciences), Chiara Panciroli (Educational processes) and Paolo Somigli (Performing arts). With the title Educating to Art / The Art of Educating, the 2022 edition focused on the tools for the education in the visual and performing arts, which are constantly evolving thanks to the constant development of digital environments and technologies in the post-pandemic phase. [read more]